Embracing Fintech Utilization: The Surge of e-Money and Internet User - Dwi Eko Waluyo (LPPM Universitas Sains dan Teknologi Komputer, 2022)
This paper discusses the relationship of electronic money transactions on Internet users in Indonesia, main of the indications of fintech utilization. This study analyzes the trends of development of the volume and value of electronic money transactions as well as the increase of internet users in Indonesia. Data were collected from 2008 to 2020. The analysis is carried out using an polinomial trend analysis. Correlation test was also conducted on the electronic money transactions and data of Internet users and its growth rate. The analysis showed that electronic money transactions and internet users growing polinomially. The strong correlation was found between internet users and GDP and also electronic money transactions. It was also found that the growth of internet users affects the growth of the value of e-money transactions, while the growth of GDP affects the growth of the volume of e-money transactions. These findings signifies the growing enthusiasm for embracing fintech in Indonesia.